Left atrial remodelling, mid-regional pro-atrial natriuretic peptide, and prognosis across a range of ejection fractions in heart failure. (1st May 2020) - Putko, Brendan N; Savu, Anamaria; Kaul, Padma; Ezekowitz, Justin; Dyck, Jason R; Anderson, Todd J; White, James A; Paterson, D Ian; Thompson, Richard B; Oudit, Gavin Y
Abstract: Aims : Measures of structural and functional remodelling of the left atrium (LA) are emerging as useful biomarkers in heart failure (HF). We hypothesized that LA volume and its contribution to stroke volume (SV) would predict a composite endpoint of HF hospitalization or death in patients with HF. Methods and results : We recruited 57 controls and 86 patients with HF, including preserved and reduced left ventricular ejection fraction (LVEF). Cardiac magnetic resonance imaging was used to evaluate LA volumes and contribution to LV SV. Plasma mid-region pro-atrial natriuretic peptide (MR-proANP) was evaluated. LA volume was negatively correlated with LVEF ( P = 0.001) and positively correlated with LV mass in HFrEF ( P < 0.001) but not in HFpEF. LA volume at end-diastole was associated with the composite endpoint in HFrEF (hazard ratio 1.26, 95% confidence interval 1.01–1.54; P = 0.044), but not HFpEF (1.06, 0.85–1.30; P = 0.612), per 10 mL/m increase. Active contribution to SV was negatively associated with the composite endpoint in HFpEF (0.32, 0.14–0.66; P = 0.001), but not HFrEF (0.91, 0.38–2.1; P = 0.828) per 10% increase. MR-proANP was associated with the composite endpoint in HFpEF (1.46, 1.03–1.94; P = 0.034), but not in HFrEF (1.14, 0.88–1.37; P = 0.278), per 100 pM increase. Conclusion : We found different relationships between LA remodelling and biomarkers in HFrEF and HFpEF. Our results support the hypothesis that the pathophysiologic underpinnings of HFpEF and HFrEF are different, and atrial remodelling encompasses distinct components for each HF subtype.